Deciphering Biological Processes at the Tick-Host Interface Opens New Strategies for Treatment of Human Diseases - Štibrániová, Iveta; Bartíková, Pavlína; Holíková, Viera; Kazimírová, Mária (Frontiers in Physiology, 2019)
Ticks are obligatory blood-feeding ectoparasites, causing blood loss and skin damage in their hosts. In addition, ticks also transmit a number of various pathogenic microorganisms that cause serious diseases in humans and animals. Ticks evolved a wide array of salivary bioactive compounds that, upon injection into the host skin, inhibit or modulate host reactions such as hemostasis, inflammation and wound healing. Modulation of the tick attachment site in the host skin involves mainly molecules which affect physiological processes orchestrated by cytokines, chemokines and growth factors. Suppressing host defense reactions is crucial for tick survival and reproduction. Furthermore, pharmacologically active compounds in tick saliva have a promising therapeutic potential for treatment of some human diseases connected with disorders in hemostasis and immune system. These disorders are often associated to alterations in signaling pathways and dysregulation or overexpression of specific cytokines which, in turn, affect mechanisms of angiogenesis, cell motility and cytoskeletal regulation. Moreover, tick salivary molecules were found to exert cytotoxic and cytolytic effects on various tumor cells and have anti-angiogenic properties. Elucidation of the mode of action of tick bioactive molecules on the regulation of cell processes in their mammalian hosts could provide new tools for understanding the complex changes leading to immune disorders and cancer. Tick bioactive molecules may also be exploited as new pharmacological inhibitors of the signaling pathways of cytokines and thus help alleviate patient discomfort and increase patient survival. We review the current knowledge about tick salivary peptides and proteins that have been identified and functionally characterized in in vitro and/ or in vivo models and their therapeutic perspective.